The Effect Of Passion Fruit (Passiflora edulis) Extract Administration on The Sex Ratio Of Mice (Mus musculus) - Bahmid, Nur Alif; Samodr, Naila Cahyani Kusuma Astuti; Aprilia, Eka; Iriani, Annisa; Augusta, Elphan (Hasanuddin University, 2025)
Passion fruit is known for its rich nutritional content. It contains several antioxidants that may influence the reproductive system of animals. Among these antioxidants is chrysin, a flavonoid compound abundantly present in passion fruit. This study aimed to determine the effect of passion fruit (Passiflora edulis) extract on the sex ratio of mice (Mus musculus) and to identify the optimal dose that may influence the proportion of male offspring. The research was conducted at the Animal Laboratory and Reproduction Laboratory of the Veterinary Teaching Hospital, Hasanuddin University, from May to July 2025. A total of 72 mice were divided into four groups: a control group (K0) and three treatment groups (P1, P2, P3) that received Passiflora edulis extract at doses of 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW, respectively, administered orally for 28 days. Data on the offspring sex ratio were analyzed using ANOVA with a 5% significance level. The results showed that groups P1 and P2 tended to have a higher proportion of male offspring compared to the control, with the highest ratio observed in P2 (1.56 ± 0.97). However, the difference among treatments was not statistically significant (P>0.05). This trend may be associated with the presence of chrysin, a flavonoid compound in passion fruit that functions as an antioxidant and aromatase inhibitor, potentially enhancing Y-sperm viability and testosterone levels. In conclusion, the administration of Passiflora edulis extract tended to increase the proportion of male offspring, although the results were not statistically significant. Further research with a larger sample size, longer treatment duration, and tighter control of female reproductive variables is needed to confirm these findings. Keywords: Chrysin, mice, passion fruit, sex ratio